Chapter 3: Citizenship Education: Rangatahi Electoral Participation - Tawhai, Veronica (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: elections; rangatahi; tiriti o waitangi/treaty of waitangi; voting

Chapter Thirteen: New Māori Politics 1990s-2000s - Bargh, Maria (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"--Publisher's information.
Keywords: elections; government relations; history; iwi; iwi chairs forum; kāwanatanga; mana party; māori electorates; māori seats; social conditions; te pāti māori; tikanga | indigenous law; tāngata whenua; voting

Effecting Change Through Electoral Politics: Cutlural Identity and the Māori Franchise - Sullivan, Ann (Journal of the Polynesian Society, 2012)
Keywords: economic development; māori seats; social development; tino rangatiratanga; voting

Dynamic and Interesting Events: The Nineteenth-Century Māori Elections - Warbrick, Paerau (New Zealand Journal of History, 2019)
The article discusses the history of the political participation of the Maori people of New Zealand in the 19th century which started with the creation of the Maori seats of Parliament under the Maori Representation Act 1867 (MRA). Topics discussed include the incorporation of MRA into the Electoral Act of 1893, the history of their voting rights, practices and election participation, and the issue of giving fair representation to Maori in the House of Parliament in 1862.
Keywords: government relations; history; māori seats; voting

Comparative Constitutional Law and Indigenous Peoples: Canada, New Zealand and the USA - Claire Charters (Comparative Constitutional Law, 2011)
Keywords: constitution; crown law; crown policy; kāwanatanga; voting

The State of Māori rights - Mutu, Margaret (Huia, 2015)
The State of Maori Rights brings together a set of articles written between 1994 and 2009. It places on record the Maori view of events and issues that took place over these years, issues that have been more typically reported to the general public from a 'mainstream' media perspective. It is an important documentation of these fifteen years of New Zealand history, recording the assertion of Maori rights as the indigenous people of Aotearoa New Zealand, focusing on Maori issues and experiences and written from a Maori perspective.
Keywords: civil Rights; colonisation; crown violence; foreshore and seabed act 2004; government relations; intergenerational trauma; kāwanatanga; mana motuhake; māori electorates; māori rights; race relations; racism; te pāti māori; tiriti o waitangi/treaty of waitangi; voting; waitangi tribunal

Multiple sites of Māori political participation - Bargh, Maria (Australian Journal of Political Science, 2013)
This article examines what might be included in a definition of Māori political participation that moves beyond a predominant focus on voting in New Zealand general elections. I suggest that the proliferation of Māori governance organisations in recent years means that Māori participation within these organisations must also be considered as part of wider political participation. In addition, I argue that Māori engagement with local authorities deserves further close examination to explore the multiple ways in which political participation occurs. Using a broader definition of Māori political participation and highlighting its many facets indicate that Māori engage in more varied ways in New Zealand politics than previously recognised
Keywords: kāwanatanga; local government; local politics; political participation; tino rangatiratanga; voting

Opportunities and complexities for Māori and mana whenua representation in local government - Bargh, Maria (Political Science, 2016)
In this article, I outline the existing legislative options available and rationale for M?ori representation in local government. I suggest that the arguments and rationale against M?ori representation have been exacerbated by a lack of clarity around local government?s duties and obligations stemming from the principles of the Treaty of Waitangi. In the second part of this article, I explore more recent arguments by M?ori for representation and involvement in local government decision-making on the basis of being mana whenua, which means to have territorial authority and power associated with the possession and occupation of tribal land. This argument foregrounds specific iwi (tribes) as holding territorial authority and therefore rights to representation and involvement in decision-making sourced in tikanga M?ori (M?ori law), over and above other M?ori who live in that area. I examine in detail the Rotorua District Council?s establishment of the Te Arawa Partnership Board in 2015 and argue that this Board and its first election results provide unique insights into the relationship between Te Arawa people living in and outside the district and has implications for broader conversations about the rights of M?ori living away from their tribal areas.
Keywords: kāwanatanga; local government; mana whenua; political participation; racism; representation; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty principles; voting

Identity and demographics predict voter enrolment on the Māori electoral roll: Findings from a national sample - Greaves, Lara; Osborne, Danny (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2017)
Keywords: identity; māori electorates; voting; voting enrolment

Māori, a politicized identity: Indigenous identity, voter turnout, protest, and political party support in Aotearoa New Zealand - Greaves, Lara M.; Sengupta, Nikhil K.; Townrow, Carly S.; Osborne, Danny; Houkamau, Carla A.; Sibley, Chris G. (International Perspectives in Psychology: Research, Practice, Consultation, 2018)
Political struggles are important to the identities of many indigenous peoples. This article examines identity as a predictor of crucial political outcomes—voter turnout, support for protest, and political party support—for Māori, the indigenous peoples of Aotearoa (New Zealand). We analyzed data from a national probability sample of Māori (N = 663) that included a scale of subjective identification with various aspects of Māori identity: the Multidimensional Model of Māori Identity and Cultural Engagement. Use of the scale allowed us to examine the facets of ethnic identity that predict political mobilization for indigenous peoples. As expected, the identity domain relating to political struggle, Socio-Political Consciousness, was positively associated with support for left-wing parties and Māori rights protest but negatively associated with support for the right-wing party. However, Socio-Political Consciousness did not relate to voter turnout. These results demonstrate the importance of ethnic identity as a key predictor of political behaviors for indigenous peoples. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: civil Rights; ethnic identity; kāwanatanga; political participation; political parties; voter turnout; voting